Pelayanan Referensi di Perpustakaan Universitas Terbuka - Rakhmawati, Nazua Sukma; Gumilau, Farahdilla; Purwanti, Herni; Azzahra, Mutia; Hidayat, Parhan (Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Reference services are one of the services available at Open University (UT) Library, and they are widely used to meet the information needs of its users. This research aims to determine the reference service process at UT Library, the process of utilizing these services, and the challenges faced in UT Library reference service. The method used is qualitative with a case study approach. Data collection techniques are through observation and interviews with subjects, namely librarians, and objects, namely UT Library reference services. The research results show that UT Library has offline reference services in the library, online reference services via specific platforms, and digitally on the UT Digital Library website. UT Library reference services are mainly utilized online and digitally through the library's online database, although offline services are still available in the UT Library building. The three primary services in the UT Library database are OER/SUAKA-UT, RBV, and E-Resources, which can be visited via the https://pustaka.ut.ac.id/lib/ page and the http://repository.ut.ac page. id/ for UT repository. Because UT Libraries prioritizes their distance services, the challenges come from the uneven distribution of information and network problems in some areas when users access digital services. That is why the distribution of information in UT Digital Library needs to be improved, as well as features that can connect users to librarians directly. This makes it easier for users who want to consult further directly with a librarian.